Multifunctionally-doped PEDOT for organic electrochemical transistors - Carli, Stefano; Bianchi, Michele; Di Lauro, Michele; Prato, Mirko; Toma, Andrea; Leoncini, Marco; De Salvo, Anna; Murgia, Mauro; Fadiga, Luciano; Biscarini, Fabio (Frontiers in Materials, 2022)
Organic Electrochemical Transistors (OECTs) are suitable for developing ultra-sensitive bioelectronic sensors. In the OECT architecture, the source-drain channel is made of a conductive polymer film either cast from a formulated dispersion or electrodeposited from a monomer solution. The commercial poly(3,4-ethylenedioxidethiophene)/poly(styrene sulfonate) (PEDOT:PSS) water dispersion is the workhorse of organic bioelectronics for its high conductance, low impact and ease of processability. In this study, a hybrid OECT channel fabrication strategy is presented, where electrochemical deposition of a PEDOT/X (with X indicating the counterion) is performed on a dispersion-cast PEDOT:PSS film. Six different counterions where used: X = PSS, Nafion, Hyaluronate, Dextran sulfate, Dexamethasone phosphate and tauroursodeoxycholic acid, each potentially endowing OECT with additional functions such as ion exchange and pharmacological activity upon release of X. The PEDOT/X-PEDOT:PSS bilayers were characterized by means of electrochemical impedance spectroscopy (EIS), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS) and focused ion beam tomography combined with scanning electron microscopy (FIB-SEM). In addition, their respective OECTs were characterized and compared to PEDOT:PSS OECT. Our results show that the hybrid bilayer strategy is viable to fabricate multifunctional OECTs with biologically-relevant function, thereby retaining the outstanding figures of merit of commercial PEDOT:PSS.